How Accurately Can Parents Judge Their Children’s Boredom in School? - Nett, Ulrike E.; Daschmann, Elena C.; Goetz, Thomas; Stupnisky, Robert H. (Frontiers in Psychology, 2016)
The purpose of the present study was to explore what parents know about their children’s boredom in school; specifically, the frequency, intensity, and antecedents of their children’s boredom, as well as how they cope with boredom. A questionnaire was administered to 437 grade 9 students (54% female, Mage = 14.82) and their parents (72% mothers, 14% fathers, 12% both parents, Mage = 45.26) measuring variables related to students boredom in mathematics class. Three different measurements were used to evaluate the accuracy of parents’ judgments: (1) the correlation between parents’ and students’ answers, (2) the mean differences between parents’ and students’ answers, and (3) the mean values of absolute differences of parents’ and students’ answers. The results suggest that parents generally have an informed knowledge about their child’s boredom and related facets. This is reflected by a mean correlation of medium size (r ̅ = .34) and a small mean effect size of the difference between parents’ and students’ judgments over all items (d ̅ = .20). Parents are also substantially better in judging their children’s boredom compared to guessing for all variables (mean effect size of d ̅ = .65). They had the most precise judgments for the frequency and intensity of boredom. The antecedents of boredom (e.g. characteristics of instruction) were also well estimated by parents; specifically, parents tend to have a bias in favor for their children evidenced by overestimating antecedents that cannot be influenced by the students and underestimating those that can be influenced by the students. The least concordance was found between parents’ and children’s perception of boredom coping strategies (e.g. accepting boredom), implying that parents lack information about how their children intentionally cope with boredom.Implications for research on student boredom are discussed as well as practical applications involving parents in boredom prevention.